2022
DOI: 10.15537/smj.2022.43.2.20210464
|View full text |Cite
|
Sign up to set email alerts
|

Does lymph node ratio (metastasis/total lymph node count) affect survival and prognosis in gastric cancer?

Abstract: Objectives: To investigate the influence of the metastatic lymph node/total lymph node ratio (N-ratio) on survival and prognosis in surgically treated gastric carcinomas. Methods:A retrospective review of 73 patients who underwent curative resection at the Department of General Surgery, Hitit University Faculty of Medicine, Turkey. Receiver operating characteristic analysis was used to calculate the cut-off value for the N-ratio of the patients. The N-ratio cut-off value was determined to be 0.32. Patients wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…Although LNM was the direct reason for distant metastases, it reflects the biological selection of more aggressive subpopulations showing close relation with local and/or regional recurrence [ 3 , 4 ]. As demonstrated by many researchers, the presence of LNMs is associated with decreased postoperative survival in gastric cancer [ 5 , 6 ], being the most important prognostic factors [ 7 ]. Because the increased rate of early detection in gastric cancer can lead to an improved prognosis, the concentrations on improving patients' quality of life and utilizing minimally invasive treatments have increased [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Although LNM was the direct reason for distant metastases, it reflects the biological selection of more aggressive subpopulations showing close relation with local and/or regional recurrence [ 3 , 4 ]. As demonstrated by many researchers, the presence of LNMs is associated with decreased postoperative survival in gastric cancer [ 5 , 6 ], being the most important prognostic factors [ 7 ]. Because the increased rate of early detection in gastric cancer can lead to an improved prognosis, the concentrations on improving patients' quality of life and utilizing minimally invasive treatments have increased [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…26 Thus, the CNP group was able to obtain higher numbers of LNs, which is consistent with the results [WMD = 6.67, 95% CI: (3.71-9.62), P < .01] in our meta-analysis. Previous studies 27,28,29 showed that a larger number of LN dissections was associated with better long- term survival of patients with GC. Therefore, CNP-trace-guided radical gastrectomy may have a better prognosis.…”
Section: Discussionmentioning
confidence: 95%
“…However, LNMR values of 100% and 50% may better differentiate prognoses. Previous studies have shown that LNMR has a significant advantage over N staging in predicting the prognosis of GC [ 21 , 22 ]. Moreover, considering that the developed system may be more applicable to evaluating patients after their first diagnosis, we did not include treatment information to guide the selection of treatment plans.…”
Section: Discussionmentioning
confidence: 99%